Ensinar e aprender transformações isométricas no ensino médio - Freitas, Ana Lúcia Viveiros de (2010)
This present work has as aim to build, discuss and evaluate the construction of a HLT related to the theme Isometries. We elected as questions of research: investigate through researches in the field of Mathematical Education, how could contribute for learning organization of Isometries and also analyse the performance of teachers of Mathematics related to activities of learning planning of Isometries in a compatible way with constructivist perspective of learning. It´s been based on Simon´s researches (1995) about elaborating Hypothetical Learning Trajectories (HLT). It´s been a qualitative research that involves two teachers of Mathematics in two public schools in São Paulo State and their work close to 58 students from High School second grade. Among the found results we selected: (a) the elaboration of a HLT is a task that is more suitable to researchers than teachers; (b) the usage of researches in Mathematical Education allows teachers to elaborate activities in order to face their difficulties, however it is necessary to think about how the teachers could access them; (c) the elaboration of activities which have constructivist perspectives aren´t enough in order to make it happen according to this aspect once the performance of the teacher has a decisive role in that process; (d) the usage of new technologies reinforce the understanding of concepts but it´s been a strategy still little used for the teachers